Visible Laser on Silicon Optofluidic Microcavity. Issue 5 (24th March 2020) - Omran, Haitham; Sameh, Mohab; Mahfouz, Ahmed; Saad, Omar; Abou Kana, Maram T. H.; Marty, Frédéric; Khalil, Diaa; Bourouina, Tarik; Sabry, Yasser M.
Abstract: Optical readout within microfluidic chips is a bottleneck limiting their industrial development. The integration of lasers operating in the visible range within a microfluidic platform is crucial for enabling in situ optical measurements in lab‐on‐a‐chip applications. In principle, microstructured single‐crystal silicon is an excellent optofluidic platform, which allows integration of microfluidic channels together with optical circuits including micro‐optics, waveguides, and resonant cavities. However, the silicon absorption below 1.1 µm is a fundamental limit that prohibits the use of silicon‐based microcavities as the feedback element for visible lasers and restricts their use to the infrared only. In this work, an ultra‐wide band silicon cavity enabled by two deeply etched hollow‐core planar waveguides is demonstrated. The proposed microcavity shows a broad bandwidth extending from 500 to 1600 nm with quality factors up to 2067. A tubular microfluidic channel is inserted between the mirrors of the optofluidic cavity. The microfluidic channel is filled with Rhodamine 6G (R6G) at 20 µL min −1 flow rate allowing successful demonstration of lasing on silicon at 562.4 nm. The laser beam propagates in‐plane (along the chip surface) and is handled with monolithically integrated input/output optical fiber grooves. This provides a unique silicon platform integrating hollow core optofluidic channels together with optical cavities, which is suitable for implementing optical readout in lab‐on‐a‐chip devices. Abstract : This work demonstrates an ultra‐wide band silicon cavity enabled by two deeply etched hollow‐core planar waveguides. The microcavity shows a bandwidth extending from 500 to 1600 nm with quality factor up to 2067. The cavity provides optical feedback for Rhodamine 6G in a microfluidic channel at 20 µL min −1 flow rate allowing successful demonstration of lasing on silicon at 562.4 nm.